GPTBot Development for Translation Purposes: Flowchart, Practical Case and Future Prospects - Helena Ortiz-Garduño; Daniel Torres-Salinas (Journal of Language and Education, 2025)
Background: This paper explores the development and evaluation of a GPTBot tailored for institutional translation tasks. It addresses a gap in applied research on how generative AI can be adapted for domain-specific translation workflows, particularly in academic institutions.